UPAYA GURU PAI MENANGGULANGI KEMALASAN BELAJAR AL-QUR’AN SISWA SD SELAMA PANDEMI COVID-19 DI KABUPATEN BLITAR - Abidin Abidin (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2021)
The research has been  conducted on the efforts of teacher education religion of Islam to overcome laziness learning on students' school base in district Blitar during a pandemic Covid-19. This learning system was changed due to the Covid-19 pandemic from the offline learning to online learning. Many teachers feel the effectiveness of learning has decreased, students are less motivated to follow the lesson and miscommunication with student’s parent or guardian . This is what then causes children to experience laziness in learning , especially learning to read the Al-Qur’an. Research done by doing observation , interviews , and documentation . Data obtained later reduced in order to obtain several groups of answers , presented in a narrative form and concluded . The results of the research indicate that efforts are taken by teachers PAI to overcome laziness children learn to read the Al-Qur’an at the level of school base in district Blitar during a pandemic Covid-19 is changing the role of the teacher from the center of the learner into a motivator for children , Establish positive communication with student's parent, do personal approach with students, conduct  visits the student's homes regularly .